2011
DOI: 10.1016/j.jtcvs.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

One single dose of histidine–tryptophan–ketoglutarate solution gives equally good myocardial protection in elective mitral valve surgery as repetitive cold blood cardioplegia: A prospective randomized study

Abstract: One single dose of antegrade cold HTK cardioplegic solution in elective mitral valve surgery protects the myocardium equally well as repetitive antegrade cold blood cardioplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 26 publications
(30 reference statements)
5
68
0
4
Order By: Relevance
“…Mortality and morbidity rates for high-risk patients with complex congenital heart disease are relatively high; therefore, although it remains difficult, the optimal myocardial protection strategy for high-risk patients should be urgently determined (6,18). Data collected from instances in which HTK solution has been used for high-risk patients with complex congenital heart disease remains rare (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality and morbidity rates for high-risk patients with complex congenital heart disease are relatively high; therefore, although it remains difficult, the optimal myocardial protection strategy for high-risk patients should be urgently determined (6,18). Data collected from instances in which HTK solution has been used for high-risk patients with complex congenital heart disease remains rare (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Histidine has a buffer effect and may enhance the efficiency of anaerobic glycolysis, tryptophane stabilizes the cell membrane and the addition of mannitol decreases cellular oedema, whereas ketoglutarate is a precursor of nicotinamide adenine dinucleotide (6). Several studies have demonstrated the efficacy of the HTK solution based on biochemical markers or physiological evaluation in experimental models (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve myocardial protection during AVR for AS, a number of studies have been conducted including those seeking ideal routes of cardioplegic solution delivery or types of cardioplegic solution, and those determining factors related to PMI [815]. These studies, however, are limited by experimental study designs and have shown mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Although more spontaneous ventricular fibrillation after aortic unclamping had been found in adult patients receiving HTK cardioplegia, one single dose of cold HTK gives equally good myocardial protection in cardiac surgery as multidose cold blood cardioplegia (CBC). [3][4][5] Experimental studies have shown, however, that HTK solution provides inadequate cardioprotection when compared to CBC. 6,7 The relative advantage of blood cardioplegia in relation to crystalloid cardioplegia is still the subject of debate in pediatric cardiac surgery.…”
mentioning
confidence: 99%
“…Moreover, the safety of HTK used for prolonged ischemic time (over 75 minutes) has not been documented. 3,6,7 Our previous study showed that HTK solution results in less spontaneous ventricular fibrillation and lower mortality when compared to St. Thomas solution, and HTK is valid for complex congenital cardiac surgery with a prolonged cross-clamping time (105-242 minute). 11 Therefore, we wanted to compare the effect of cold HTK with that of CBC, which was assumed to be the best cardioplegia method, on a neonatal piglet model.…”
mentioning
confidence: 99%